2015
DOI: 10.1093/cid/civ708
|View full text |Cite
|
Sign up to set email alerts
|

Ryan White HIV/AIDS Program Assistance and HIV Treatment Outcomes

Abstract: Background The Ryan White HIV/AIDS Program (RWHAP) provides persons infected with human immunodeficiency virus (HIV) with services not covered by other healthcare payer types. Limited data exist to inform policy decisions about the most appropriate role for RWHAP under the Patient Protection and Affordable Care Act (ACA). Methods We assessed associations between RWHAP assistance and antiretroviral therapy (ART) prescription and viral suppression. We used data from the Medical Monitoring Project, a surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 11 publications
1
45
1
Order By: Relevance
“…15 Access to treatment does not explain this deficiency because The Ryan White HIV/ AIDS Foundation supports a successful AIDS Drug Assistance Program administered by states for low-income and uninsured people living with HIV. 16 There is little evidence of effective interventions to improve viral suppression, despite this being a critical step in the HIV care continuum as described in the National HIV/AIDS Strategy for the United States. 17e20 Promising evidence shows that financial incentives can improve adherence to treatment and viral suppression among people living with HIV.…”
mentioning
confidence: 99%
“…15 Access to treatment does not explain this deficiency because The Ryan White HIV/ AIDS Foundation supports a successful AIDS Drug Assistance Program administered by states for low-income and uninsured people living with HIV. 16 There is little evidence of effective interventions to improve viral suppression, despite this being a critical step in the HIV care continuum as described in the National HIV/AIDS Strategy for the United States. 17e20 Promising evidence shows that financial incentives can improve adherence to treatment and viral suppression among people living with HIV.…”
mentioning
confidence: 99%
“…It is also worth noting that most participants in our sample had been living with HIV for a long time and had received care in Ryan White settings prior to incarceration. National-level data from the Medical Monitoring Project demonstrate that patients receiving assistance from Ryan White funding have better care outcomes than patients who do not receive support from Ryan White [20]. Additionally, all participants in our study self-reported that they were taking ART at the time of release and described their housing situation as at least "comfortable."…”
Section: Discussionmentioning
confidence: 93%
“…•Adds annual limits on beneficiary out-of-pocket costs (including any cost-sharing or coinsurance obligations, but excluding premiums) for individual and family coverage •Removes annual and lifetime limits on plans' coverage for essential health benefits [3]. Estimates from Health Resources and Services Administration (HRSA) suggest that almost 27.6 % of those who received services through the Ryan White program in 2012 were uninsured [4].…”
Section: Section 2001mentioning
confidence: 99%
“…Because both systems are limited to PLWH who sought healthcare or support services, these estimates are likely to underestimate the percentage of all PLWH who lack health insurance. Moreover, at least 40 % of HIV-infected adults in medical care received health insurance through Medicaid and/or Medicare, programs for which they generally qualified only once their disease was sufficiently advanced that they became eligible for disability benefits under Social Security [3]. Determining insurance coverage among persons at high risk for acquiring HIV is even more difficult, as the estimates will vary according to a host of conceptual (e.g., the definition of Brisk^used) and methodological (e.g., the sampling methods employed) factors.…”
Section: Section 2001mentioning
confidence: 99%